ANALISIS KESULITAN MENULIS TEGAK BERSAMBUNG BAHASA INDONESIA PADA SISWA KELAS II DI SD IT AL- BARIZA - Resmiyani, Melisa; Risma Nuriyanti; Dani Gunawan; Teguh Susilo, Setiadji (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the difficulties faced by second-grade elementary school students in writing connected print letters. The difficulties identified include writing capital letters, combining letters into words, and inconsistencies in the shape and size of letters. The contributing factors are psychological, motor skills, and social aspects. This study aims to analyze the difficulties in writing connected print letters among second-grade students at SD IT AL-Bariza. The research method used is qualitative with a case study approach. The subjects of this study consist of second-grade students and their classroom teacher. Data collection techniques include observation, interviews, and documentation. Observations were conducted to identify students experiencing difficulties and to assess their writing skills at school. Interviews were used to obtain information from teachers and students. Documentation includes samples of students' writing in lined notebooks.